Editorial: The Need for Good Leaders in Higher Education - Crawford, Joseph (Journal of University Teaching and Learning Practice, 2023)
Consistently, and without pause, have ethical, social, and moral crises plagued the higher educational domain. With rapidly changing student bases, staff profiles, and funding structures, university leaders and managers have been required to do, and be, more. In times of crisis, heightened complexity, and competition, leaders have struggled with greater frequency to be, and do, good. In parallel, students and learners have juggled more, had more diverse motivations for studying, and been less homogenous with the once-typical nineteen-year-old recent high school graduate. In recent years, there have been repeated stories of unethical practices of leadership. While catastrophising is not the aim, nor pursuit, of this editorial, these provide context for the Journal’s expansion into educational leadership, management, and educational psychology in higher education. With the rise of software to make cheating easier, opportunities to outsource dissertations, and a more turbulent sector, it will be the leaders who sustain teams, and build good educational outcomes.